Congenital tibial pseudarthrosis, changes in treatment protocol. Issue 5 (September 2015) - Shabtai, Lior; Ezra, Eli; Wientroub, Shlomo; Segev, Eitan
<x xml:space="preserve">Abstract</x> Ten children with congenital pseudarthrosis of the tibia were treated with resection of pathologic bone, bone grafting, intramedullary rodding, compression with circular frame, simultaneous proximal tibia lengthening, and bone morphologic proteins. Thirteen operations were performed to achieve union. Four patients underwent simultaneous lengthening and four patients received recombinant human bone morphologic protein. Six children required complementary operations for residual ankle and knee valgus, and shortening. Union of the pseudarthrosis was achieved in all cases with lengthening up to 5 cm. This protocol is effective in achieving union of congenital pseudarthrosis of tibia; attention should be paid to the ankle joint to achieve functionality of the limb.